Soft Tissue Tumours with Epithelioid Morphoogy - Muhammad Zain Mehdi, Sajid Mushtaq, Noreen Akhtar, Usman Hassan, Asif Loya, Mudassar Hussain; Muhammad Azam (Journal of Rawalpindi Medical College, 2017)
To study the morphological findings of soft tissue sarcomas with epithelioid morphology and their distribution with respect to the age, gender and location.